The Ruggie Framework, Business Human Rights Self-Regulation and Tort Law: Increasing Standards through Mutual Impact and Learning. Issue 1 (2nd January 2017) - Glinski, Carola
ABSTRACT: This article discusses the relationship between John Ruggie's 'Protect, Respect and Remedy Framework' and the UN 'Guiding Principles on Business and Human Rights', tort law and transnational business human rights self-regulation. In a first step, it highlights the parallels between the recent attempts to introduce human rights obligations to transnational corporations, as laid down in the Ruggie Framework and Guiding Principles, with tort law principles, doctrine and interpretation. It thereby considers recent developments related to the specific responsibilities of parent companies for their subsidiaries' activities and of core companies for their supply chains. In a second step, it conceptualises the potential for progressive mutual impact and mutual learning, not only between tort law and public international soft law, but especially with regard to the legal effects of transnational self-regulatory regimes like codes of conduct and best practices. The article elaborates that these transnational self-regulatory regimes and best practices have the capacity to constitute legal minimum standards of care and, in particular, standards concerning corporation-wide or supply chain-wide tortious responsibility. As a consequence, the interplay between the Ruggie Framework and Guiding Principles, transnational business self-regulation and tort law could lead to an upward helix development of the consideration of human rights in corporate practice and in raising legal requirements for parent and core companies.